Cabazes de Nostalgia e Retóricas do Mar entre Malaca e Portugal - Pires, Ema Cláudia (Trabalhos de Antropologia e Etnologia, 2020)
This text discusses relations between processes of objectification of the past, identity construc tions and ways of living the present and imagining the future. Methodologically, the analysis stems from continuing ethnography in Portugal and Malaysia. Specifically, we discuss the relationship between experiences and expectations of/about a Creole group resident in Peninsular Malaysia that traces its origins to a genealogy of several centuries dating back to a Portuguese ancestry. Based on this analytical locus, it is shown how different categories of people, including expectations and everyday experiences, weave their lives intertwined in imaginary ideas of past and future.